Impact of peer support on inpatient and outpatient payments among people with Type 2 diabetes: a prospective cohort study. Issue 6 (16th April 2018) - Yu, D.; Graffy, J.; Holman, D.; Robins, P.; Cai, Y.; Zhao, Z.; Simmons, D.
Abstract: Aim: To investigate the impact of a low‐cost diabetes peer‐support intervention, aimed at reducing inpatient and outpatient care utilization and healthcare payments, by conducting a cohort study that followed up a randomized controlled trial. Methods: A total of 1121 adults with Type 2 diabetes were recruited through general practices in Cambridgeshire and Hertfordshire, UK, and were followed up for 3.25 financial years after 8–12 months of one‐to‐one, group or combined diabetes peer support and usual care. Use of, and payments for inpatient and outpatient services were fully recorded in the follow‐up. Adjusted mean inpatient and outpatient payments per person were estimated using a two‐part model after adjusting for baseline characteristics. Results: The mean age of the recruited adults was 65.6±11.4 years, 60.4% were male, and 16.8% were insulin‐treated. Compared with the control group, less healthcare utilization (especially non‐elective inpatient care and outpatient consultations) was observed in each of the intervention groups, particularly the combined intervention group. Over the course of 3.25 financial years, significant reductions of 41% (£909.20 per head) were observed for overall inpatient payments ( P <0.0001), 51% (£514.67 per head) for non‐elective inpatient payments ( P =0.005) in the combined intervention group, and 34% (£413.30 per head) and 32% (£388.99 per head) for elective inpatient payments in the one‐to‐one ( P =0.029) and combined intervention ( P =0.048) groups, respectively. Conclusions: Type 2 diabetes peer support, whether delivered using a one‐to‐one, group or combined approach was associated with reduced inpatient care utilization (particularly non‐elective admissions) and payments over 3.25 years. What's new?: Peer support, whether delivered using a one‐to‐one, group or combined approach, was associated with reduced inpatient care utilization and payments. An intervention that combined individual and group peer‐support had a consistent and potentially long‐term impact on health payments. These data support the incorporation of invitation to structured peer support into modern Type 2 diabetes management. A two‐part model adjusting patients' potential probability of utilising the health system is a practical tool to evaluate the health payment accurately.